2021
DOI: 10.1186/s12966-021-01087-x
|View full text |Cite
|
Sign up to set email alerts
|

School-based gardening, cooking and nutrition intervention increased vegetable intake but did not reduce BMI: Texas sprouts - a cluster randomized controlled trial

Abstract: Background Although school garden programs have been shown to improve dietary behaviors, there has not been a cluster-randomized controlled trial (RCT) conducted to examine the effects of school garden programs on obesity or other health outcomes. The goal of this study was to evaluate the effects of a one-year school-based gardening, nutrition, and cooking intervention (called Texas Sprouts) on dietary intake, obesity outcomes, and blood pressure in elementary school children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
108
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(114 citation statements)
references
References 69 publications
4
108
0
2
Order By: Relevance
“…The outcomes, such as children’s knowledge of fruits and vegetables, intake preference, and intake motivation, could not accurately measure the changes of children’s FVs. Therefore, some researchers use a 24 h food diary (CADET) or Block Kids food filter to measure the changes of FVs in portions [ 23 , 25 , 26 , 47 , 53 ]. Among them, Christian’s [ 23 ] and Davis’ [ 53 ] studies had the most significant effects and showed an increase in the children’s FVs by about 1.4 and 0.8 portions through 72 weeks and 36 weeks of SGA and other interventions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The outcomes, such as children’s knowledge of fruits and vegetables, intake preference, and intake motivation, could not accurately measure the changes of children’s FVs. Therefore, some researchers use a 24 h food diary (CADET) or Block Kids food filter to measure the changes of FVs in portions [ 23 , 25 , 26 , 47 , 53 ]. Among them, Christian’s [ 23 ] and Davis’ [ 53 ] studies had the most significant effects and showed an increase in the children’s FVs by about 1.4 and 0.8 portions through 72 weeks and 36 weeks of SGA and other interventions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some researchers use a 24 h food diary (CADET) or Block Kids food filter to measure the changes of FVs in portions [ 23 , 25 , 26 , 47 , 53 ]. Among them, Christian’s [ 23 ] and Davis’ [ 53 ] studies had the most significant effects and showed an increase in the children’s FVs by about 1.4 and 0.8 portions through 72 weeks and 36 weeks of SGA and other interventions, respectively. While in Morgan’s [ 26 ] and Hanbazaza’s [ 47 ] studies, after 10 and 72 weeks of SGA, the FVs increased only by 0.2 and 0.4 portions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations